1983
DOI: 10.1149/1.2120109
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pressure on the Product Distribution in Kolbe Electrolysis

Abstract: Experiments have been run which demonstrate that electrochemical oxidation ofn-alkanoic acids (in the range of C4-C6) in aqueous solution at a smooth platinum anode gives higher yields of alkane dimer product when run at elevated pressures than an equivalent experiment at atmospheric pressure. This phenomenon has been observed over awide range of reaction conditions. A plausible explanation for this result is that under high pressure conditions, olefin accumulates at the anode surface which helps to prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…Furthermore, polar groups (e.g.,s ulfates from Na 2 SO 4 )c ould also promote ester formation as they may stabilize carbocation intermediates. [34] On the other hand, most of the Kolbe electrolysis products will accumulate in the organic phase, simplifying the downstream process in terms of product processing and facilitating supporting electrolyte recycling.…”
Section: Economic Consideration Of Using Supporting Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, polar groups (e.g.,s ulfates from Na 2 SO 4 )c ould also promote ester formation as they may stabilize carbocation intermediates. [34] On the other hand, most of the Kolbe electrolysis products will accumulate in the organic phase, simplifying the downstream process in terms of product processing and facilitating supporting electrolyte recycling.…”
Section: Economic Consideration Of Using Supporting Electrolytesmentioning
confidence: 99%
“…[30,33] Many studies were dedicated to the detailed understanding on how different input parameters, such as pH or reactantc oncentration, influence the Kolbe electrolysis. Unfortunately,h owever,t ot he best of our knowledge, it was commonly not considered that whenever one of theseparametersi schanged, at least one further key parameter is affecteda tt he same time:t he electrolytic conductivity, k.For example, if the concentration of the reactant is increased, [29,[33][34][35][36] the total number of ions is increased, or if the temperature is increased, ion movement is accelerated, both resultingi na ni ncreased electrolytic conductivity. Therefore, it cannot be ascertained whether ad ifference in yield or turnover rate is either ar esult of the change of the target parameter or the change in conductivity.U nfortunately, values of conductivities of electrolyte solutionsa re rarely reported for electroorganic syntheses in general,a nd Kolbe electrolysis in particular.F urther,a ss etups of different dimensions, geometries, and electrode surface-to-volume ratios were applied for studying and engineering Kolbe electrolysis, an assessment of the influence of the k is thus not possible so far.…”
Section: Introductionmentioning
confidence: 99%
“…Decarboxylation at the anode releases an electron and generates a reactive alkyl radical that may either combine to form alkanes (Kolbe reaction) or oxidize further to a carbonium ion that converts to alcohols, alkenes, or esters. Pioneering work by Sanderson et al ( 1983 ) demonstrated high yields of C 6 -C 10 alkanes from C 5 and C 6 VFA solutions under specialized electrochemical reaction conditions. This H 2 can be recovered for direct use as a fuel, converted to methane by methanogenic archaea, or combusted to generate electricity to drive the anodic reaction reaction, fi rst described by Kolbe ( 1849 ), is one of the oldest known reactions in organic chemistry.…”
Section: Hofer-moest Reactionmentioning
confidence: 99%
“…[8] Over time, the oxidation of carboxylates, including aliphatic and aromatic molecules, evolved to become one of the best characterized electroorganic reactions. [7,[9][10][11][12][13][14][15][16][17][18] Note that the carboxylate, i. e. the carboxylic acid anion, is the starting compound of the electrochemical reaction [7] (see also Figure S1). Yet in literature, "carboxylic acid" is often used as a general term in this context, not distinguishing the protonation states of the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive descriptions of the numerous reaction pathways of carboxylate oxidation are available, also summarizing the preferred reaction mechanism in dependency of, i. e., the solvent (polar vs. nonpolar, protic vs. aprotic), the electrode material (e. g. platinum, graphite, gold or glassy carbon), the applied working electrode potential or the applied current density, the educt concentration as well as the presence of additional supporting electrolytes. [7,[9][10][11][12][13][14][15][16][17][18] Among others, it was reported that a high current density, a high educt concentration (e. g. 0.5 mol L À1 ) and a neutral or slightly acidic pH promote the Kolbe-reaction over the intermediate formation of carbocations and related follow-up reactions in aqueous media (see Fig-ure S1 for the details on the example of n-octanoic acid/noctanoate). [7] Furthermore, if different carboxylates with differ-ent carbon chain lengths are present or formed during the reaction, mixed-Kolbe products, i. e. alkanes deriving from monomers of different chain length, can be formed.…”
Section: Introductionmentioning
confidence: 99%